Control del Empuje de una Barra usando dos Robots Móviles y Visión Artificial - Bacca Cortes, Eval Bladimir; Caicedo Bravo, Eduardo Francisco (Ingeniería, 2005)
This paper describes a solution to the vision based bar pushing control using two robots, which direct applications are the cooperative transport and handle of big objects. The solution proposed involves two mobile robots which position, heading and velocity are gathering through a video camera placed on scene top; each robot has an independent heading controller,which control objective is the path following previously defined; using the kinematics' differential mobile robot the bar's model and its control is obtained, the bar is pushed with help of the two robots and its trajectory is perpendicular to it. The solution described use a RST [1] digital controller for the mobile robots' heading control, with TS=0.2s, x=0.707, wN = 3.5 rd/s and a stable state error mean of 15% approximately. The bar's heading control modifies the mobile robots' lineal velocity, a PD controller was used with: KP = 2.7, KD = 0.2, x = 2.807 y wN = 3.539 rad/s and a stable state error mean of 5.1% approximately.